Improved differentiation between MS and vascular brain lesions using FLAIR* at 7 Tesla. - Kilsdonk, Iris D; Wattjes, Mike P; Lopez-Soriano, Alexandra; Kuijer, Joost P A; de Jong, Marcus C; de Graaf, Wolter L; Conijn, Mandy M A; Polman, Chris H; Luijten, Peter R; Geurts, Jeroen J G; Geerlings, Mirjam I; Barkhof, Frederik (European Radiology, 2014)
Objectives: To investigate whether a new magnetic resonance image (MRI) technique called T2*-weighted fluid attenuation inversion recovery (FLAIR*) can differentiate between multiple sclerosis (MS) and vascular brain lesions, at 7 Tesla (T).Methods: We examined 16 MS patients and 16 age-matched patients with (risk factors for) vascular disease. 3D-FLAIR and T2*-weighted images were combined into FLAIR* images. Lesion type and intensity, perivascular orientation and presence of a hypointense rim were analysed.Results: In total, 433 cerebral lesions were detected in MS patients versus 86 lesions in vascular patients. Lesions in MS patients were significantly more often orientated in a perivascular manner: 74 % vs. 47 % (P < 0.001). Ten MS lesions (2.3 %) were surrounded by a hypointense rim on FLAIR*, and 24 MS lesions (5.5 %) were hypointense on T2*. No lesions in vascular patients showed any rim or hypointensity. Specificity of differentiating MS from vascular lesions on 7-T FLAIR* increased when the presence of a central vessel was taken into account (from 63 % to 88 %), most obviously for deep white matter lesions (from 69 % to 94 %). High sensitivity remained (81 %).Conclusion: 7-T FLAIR* improves differentiation between MS and vascular lesions based on lesion location, perivascular orientation and presence of hypointense (rims around) lesions.Key Points: • A new MRI technique T2*-weighted fluid attenuation inversion recovery (FLAIR*) was investigated. • FLAIR* at 7-T MRI combines FLAIR and T2* images into a single image. • FLAIR* at 7 T does not require enhancement with contrast agents. •High-resolution 7-T FLAIR* improves differentiation between MS and vascular brain lesions. • FLAIR* revealed a central vessel more frequently in MS than vascular lesions.